2022
DOI: 10.3390/ijms231911578
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the ROS/CncC Signaling Pathway Regulates Cytochrome P450 CYP4BQ1 Responsible for (+)-α-Pinene Tolerance in Dendroctonus armandi

Abstract: Bark beetles mainly rely on detoxification enzymes to resist the host tree’s defense against oleoresin terpenes. Cytochrome P450 enzymes (CYPs) play an important role in the detoxification of plant allelochemicals and pesticides in insect. One P450 gene (DaCYP4BQ1) is associated with the response of (+)-α-pinene in Dendroctonus armandi. However, the regulatory mechanism of this P450 gene response to (+)-α-pinene is still unknown. In this study, spatiotemporal expression profiling indicated that CYP4BQ1 was hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Previous studies have reported that elevated CO 2 increases the activity of detoxifying enzymes such as carboxylesterases (CarEs) and glutathione S-transferases (GSTs) [16]. Detoxification enzymes play essential roles in the survival of insects exposed to adverse environments [19][20][21], therefore, higher detoxifying enzymes activity indicate that those enzymes may be involved in anti-eCO 2 stress, thereby changing the insecticide susceptibility in insect. However, the exact mechanism is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that elevated CO 2 increases the activity of detoxifying enzymes such as carboxylesterases (CarEs) and glutathione S-transferases (GSTs) [16]. Detoxification enzymes play essential roles in the survival of insects exposed to adverse environments [19][20][21], therefore, higher detoxifying enzymes activity indicate that those enzymes may be involved in anti-eCO 2 stress, thereby changing the insecticide susceptibility in insect. However, the exact mechanism is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [40] showed that CarE, GST, and CYP450 activity in F. occidentalis increase significantly after treatment with an LC 25 dose of spinetoram, while the activity of AChE decreases. Detoxification enzymes play essential roles in the survival of insects exposed to adverse environments [41][42][43][44]. Therefore, higher detoxifying enzyme activity indicates the involvement of those enzymes in insecticide stress, thereby changing the insecticide susceptibility in insects.…”
Section: Introductionmentioning
confidence: 99%
“…Throughout evolution, plants have developed intricate defense mechanisms to combat the threats posed by an array of phytophagous insects [1,2]. These strategies often involve the production of diverse secondary metabolites, which can be classified into four categories, sulfur-containing compounds, alkaloids, phenols, and terpenoids, which often display toxic or antifeedant effects on host insects [3][4][5]. Among these four phytochemicals, terpenoids have exceptional structural diversity.…”
Section: Introductionmentioning
confidence: 99%